Evaluation of corneal topography and higher order aberrations of the fellow eye in unilateral keratoconus - Mahmoud Mohamed Attia El Morsy; Ezz El Dein Galal Mohamed; Assad Ahmed Ibrahiem Ghanem; Ismail Ahmed Naguib Omar; Rasha Safwat Elhiny (Journal of the Egyptian Ophthalmological Society, 2023)
Purpose To assess parameters of corneal topography and higher order aberrations (HOAs) data in the apparently normal contralateral eyes of unilateral keratoconus (KC) cases in comparison with normal eyes of healthy individuals. Patients and methods This observational case-control study included 70 eyes divided into two equal groups; group A was the fellow eyes of unilateral keratoconus patients and group B included the normal control eyes. They were examined by Schimpflug camera to extract the study parameters (keratometry indices, the inferior-superior(I-S) difference at 4 mm, posterior elevation (PE), front and back difference, thickness progression index, corneal pachymetry, multimetric D index (D index), topometric indices and Zernike analysis). Results In comparing the study data between Groups A and B, we demonstrated that ISV, IVA, and CKI had no difference between the two groups. But other topometric parameters showed statistically significant differences between the two groups. Assessment of corneal aberrations revealed that the RMS HOA, vertical coma, and spherical aberrations were associated with significant increases in the apparently normal eyes of unilateral KC cases in comparison with healthy individual eyes (P<0.001). Conclusion Fellow eyes of unilateral KC cases seem not to be totally normal. And so, it is recommended to regularly examine these eyes at close intervals to catch up any abnormality and to avoid KC progression.